Microbial Turnover and Dispersal Events Occur in Synchrony with Plant Phenology in the Perennial Evergreen Tree Crop Citrus sinensis - Nichole A. Ginnan; N. Itzel De Anda; Flavia Campos Freitas Vieira; Philippe E. Rolshausen; M. Caroline Roper (mBio, 2022)
ABSTRACT Emerging research indicates that plant-associated microbes can alter plant developmental timing. However, it is unclear if host phenology affects microbial community assembly. Microbiome studies in annual or deciduous perennial plants face challenges in separating effects of tissue age from phenological driven effects on the microbiome. In contrast, evergreen perennial trees, like Citrus sinensis, retain leaves for years, allowing for uniform sampling of similarly aged leaves from the same developmental cohort. This aids in separating phenological effects on the microbiome from impacts due to annual leaf maturation/senescence. Here, we used this system to test the hypothesis that host phenology acts as a driver of microbiome composition. Citrus sinensis leaves and roots were sampled during seven phenological stages. Using amplicon-based sequencing, followed by diversity, phylogenetic, differential abundance, and network analyses, we examined changes in bacterial and fungal communities. Host phenological stage is the main determinant of microbiome composition, particularly within the foliar bacteriome. Microbial enrichment/depletion patterns suggest that microbial turnover and dispersal were driving these shifts. Moreover, a subset of community shifts were phylogenetically conserved across bacterial clades, suggesting that inherited traits contribute to microbe-microbe and/or plant-microbe interactions during specific phenophases. Plant phenology influences microbial community composition. These findings enhance understanding of microbiome assembly and identify microbes that potentially influence plant development and reproduction. IMPORTANCE Research at the forefront of plant microbiome studies indicates that plant-associated microbes can alter the timing of plant development (phenology). However, it is unclear if host phenological stage affects microbial community assembly. Microbiome studies in annual or deciduous perennial plants can face difficulty in separating effects of tissue age from phenological driven effects on the microbiome. Evergreen perennial plants, like sweet orange, maintain mature leaves for multiple years, allowing for uniform sampling of similarly aged tissue across host reproductive stages. Using this system, multiyear sampling, and high-throughput sequencing, we identified plant phenology as a major driver of microbiome composition, particularly within the leaf-associated bacterial communities. Distinct changes in microbial patterns suggest that microbial turnover and dispersal are mechanisms driving these community shifts. Additionally, closely related bacteria have similar abundance patterns across plant stages, indicating that inherited microbial traits may influence how bacteria respond to host developmental changes. Overall, this study illustrates that plant phenology does indeed govern microbiome seasonal shifts and identifies microbial candidates that may affect plant reproduction and development.